Multidrug-resistant bacteria in lung transplantation. Issue 4 (August 2020) - Dominguez, Fernando; Blodget, Emily
Abstract : Purpose of review: The review of infections in lung transplantation is beyond the scope of this article as it is a comprehensive topic, however we aim to focus on infections with multidrug-resistant (MDR) microorganisms in this patient population. Recent findings: New emerging clinical studies have provided data regarding outcomes in lung transplant recipients with MDR bacterial infections. Summary: Isolation of MDR bacteria from lung donors preoperatively has not been associated with worse outcomes in recipients. Patients with cystic fibrosis colonized with MDR bacteria do not have increased 1 year mortality rates compared to those without MDR bacteria.